PENGENALAN DAN PELATIHAN PERSUASIVE COPYWRITING BAGI KARANGTARUNA DUKUH GONDANG LEGI, JUMAPURO, DAN BRONGKOL DESA KWANGSAN DI ERA EKONOMI DIGITAL - Faraba, Karina Sofiananda Armaza; Muslimin, Edy; Hartadi, Hartadi (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Community service is held as a form of synergy of activities that are expected to be able to provide practical and versatile solutions for the community. The activities of this service program are focused on introducing and training basic persuasive copywriting as a promotional strategy in the era of the digital economy. The assisted subjects are the youth of Karangtaruna dukuh Gondang Legi, Jumapuro, and Brongkol in Karanganyar Regency. The method of conducting the midwifery is carried out in three stages, namely 1) preparation, 2) implementation, and 3) evaluation. This community service activity has a range of results, including: a) knowing and understanding the concept of persuasive copywriting, b) knowing the types of persuasive copywriting, and c) being able to make promotional sentences using persuasive copywriting techniques. From the results of making taglines or promotional sentences made with copywriting techniques, as many as 55 participants have been able to apply copywriting techniques by making promotional sentences using the same rhyme. Meanwhile, other participants are still trying to design promotional sentences. The conclusion of this service activity is that all training participants already understand about online marketing and will enthusiastically apply online marketing materials in which they review copywriting techniques so that they can attract potential consumers.